Metagenômica: busca de novos genes envolvidos com a biodegradação de hidrocarbonetos e síntese de biossurfactantes - Melo, Abinadabe Jackson de (2012)
Industrial activities, oil spills and its derivatives, as well as the incomplete combustion of fossil fuels have caused a great accumulation of hydrocarbons in the environment. The number of microorganisms on the planet is estimated at 1030 and prokaryotes the most abundant. They colonized diverse environments for thousands of years, including those considered extreme and represent an untapped source of metabolic and genetic diversity with a large biotechnological potential. It is also known that certain microorganisms have the enzymatic capacity to degrade petroleum hydrocarbons and, in many ecosystems, there is an indigenous community capable of performing this function. The metagenomic has revolutionized the microbiology allowing access uncultured microbial communities, being a powerful tool for elucidation of their ecological functions and metabolic profiles, as well as for identification of new biomolecules. Thus, this study applied metagenomic approaches not only for functional selection of genes involved in biodegradation and emulsification processes of the petroleum-derived hydrocarbons, but also to describe the taxonomic and metabolic composition of two metagenomes from aquatic microbiome. We analyzed 123.116 (365 ± 118 bp) and 127.563 sequences (352 ± 120 bp) of marine and estuarine metagenomes, respectively. Eight clones were found, four involved in the petroleum biodegradation and four were able to emulsify kerosene indicating their abilities in biosurfactants synthesis. Therefore, the metagenomic analyses performed were efficient not only in the search of bioproducts of biotechnological interest and in the analysis of the functional and taxonomic profile of the metagenomes studied as well